2022
DOI: 10.1177/03611981221130027
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Stone Processing Waste on Mechanical, Durability, and Ecological Performance of Hybrid Fiber-Reinforced Engineered Cementitious Composite

Abstract: The current study is focused on the characteristics of sustainable engineered cementitious composites (ECCs) with the inclusion of various types of fibers (PVA, PET, and MSE) in hybridization, silica sand (SS), river sand (RS), and stone processing waste (SPW). SPW is termed as hazardous material because of the presence of finer particles and inorganic substances which contribute to leaching problems, and cause adverse effects on aquatic life and human health. The objective of this study was to introduce new k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
(77 reference statements)
0
2
0
Order By: Relevance
“…The properties and dispersion amount of fibers play crucial role in the performance of ECC matrix. [11][12][13] The extensive review of previous literature exhibited that matrix of ECC mainly consists of polymeric fibers such as polyvinyl alcohol (PVA fiber), polyethylene fiber (PE), polypropylene fiber (PP). [14][15][16] The parameters of ECC revealed that it is an ideal material for plastic hinge of beam-column connections.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The properties and dispersion amount of fibers play crucial role in the performance of ECC matrix. [11][12][13] The extensive review of previous literature exhibited that matrix of ECC mainly consists of polymeric fibers such as polyvinyl alcohol (PVA fiber), polyethylene fiber (PE), polypropylene fiber (PP). [14][15][16] The parameters of ECC revealed that it is an ideal material for plastic hinge of beam-column connections.…”
Section: Introductionmentioning
confidence: 99%
“…The abovementioned properties are attained through careful customization and proportioning of the constituents in mix proportion of ECC. The properties and dispersion amount of fibers play crucial role in the performance of ECC matrix 11–13 . The extensive review of previous literature exhibited that matrix of ECC mainly consists of polymeric fibers such as polyvinyl alcohol (PVA fiber), polyethylene fiber (PE), polypropylene fiber (PP) 14–16 .…”
Section: Introductionmentioning
confidence: 99%